An Exploration on the Business Model of Social Enterprises Owned By Chinese Entrepreneurs in Taiwan - Shang-Yung, Yen; Song-Ching, Fan (Asian Economic and Financial Review, 2014)
This study aims to explore the business models of the social enterprises owned by Chinese entrepreneurs and tries to construct a business model. In order to overcome the shortcomings of a lack of objective verification in the qualitative study, for example, whether or not there is significance for the variables, and whether or not there is consistent reliability and validity of the sample, this study adopts a new qualitative study method fuzzy set qualitative comparative analysis, (fs / QCA) to conduct empirical study. The research conclusions further support the design of the model elements of the social enterprises run by Chinese entrepreneurs, we suggest that three elements (guanxi, social value proposition, and social and environmental benefits) be considered for exploration to fully explore the 10 necessary business model elements. The preliminary exploration results verify that fs / QCA could assist researchers in finding out the causal correlation among variables, determine whether or not there are necessary conditions or sufficiency conditions and have a more objective analysis tool to interpret the causal correlation of small samples. It is also another approach for social science study to complete the gap in research methods between quantitative and qualitative research.